Sosialisasi UMKM Kuliner Bibik Kuweh untuk Peningkatan Penjualan melalui Optimasi Digital Marketing - Nahdan Al Aufa; Durotul Masfufah; Sarah Tsabitah; Susi Indriyani; Annisa Giani Zahra; Dimas Dwi Farizi; Mahrinasari MS (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
Micro, Small and Medium Enterprises (MSMEs), contribute to GDP by 61%, or worth IDR 9,580 trillion, in fact the contribution of MSMEs to labor absorption reaches 97% of the total workforce. Bibik Kuweh is one of MSMEs to develop in the packaged and ready-to-eat culinary business which has been managed in Bandar Lampung since 2017. Currently, partners' biggest challenges are packaging issues and digital marketing optimization. While the package is used just as it is, the marketing strategy depends on word-of-mouth. The team that made the proposal suggested using packaging and training in digital marketing to address this issue. As a consequence of completing this community service project, partners will be able to use digital marketing, which starts with social media content and ends with social media advertising, to market their company products. In regards to packaging concerns, partner products now feature visually appealing packaging together with labels that provide information about the product.